Strategi Meningkatkan Kesejahteraan Masyarakat Berbasis Masjid : (Studi Pada Masjid Baitul Mukminin Gedangan Sidoarjo) - Mustofa Mustofa (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2020)
The purpose of this study was to determine and analyze how the strategy of the mosque in improving the welfare of the community in Gedangan District, Sidoarjo Regency? and how to increase the welfare of the community at the Baitul Mukminin Mosque, Gedangan District, Sidoarjo Regency? This type of research is descriptive qualitative, this research is classified as field research or field research. The data collection techniques used interviews, observation and documentation. Meanwhile, the data analysis technique uses the Miland Huberman model based on data reduction analysis, display data and conclusion drawing. The results of this study concluded that (1) the strategy carried out by the Baitul Mukminin Mosque to improve the welfare of the community was to form the Dhuafa Crisis Center '(CCD). There are several programs being developed, namely: (a) BAMBU (Entrepreneurial Capital Assistance); (b) PASTA (Love Dhuafa Staple Food Package '); (c) SANTAN (Education Support for Orphans); (d) DAHSYAT (Community Health Fund); (e) SEDAP (Responsive Alms); (f) MAXIFA (Lunch with Dhuafa`); (g) SAJIAN (Teacher's Benefits of Koran); and (h) Humanitarian Post. (2) From the programs run by the Crisis Center Dhuafa ', it can be seen that there is an increase in welfare that is felt by the community. The form of increased welfare is an increase in income, reduced consumption expenditure, ease of accessing health services, ease of continuing education, ease of getting a place. living and living facilities. The Dhuafa Crisis Center '(CCD) is expected to be able to maintain and develop the program optimally both in terms of raising funds and distributing it so that more and more people will be prosperous.